A current assessment of the Hamburg rules - Huber, Max (Department of Commercial Law, 2021)
Trade has been booming. The WTO ( World Trade Organisation) estimated that world trade in goods grew 8 % in volume terms last year, this being four times the growth of world GDP (Gross Domestic Products). During the 1990s international trade has grown far faster than world output, showing that national economies are becoming more closely linked. Foreign direct investment, another gauge of international economies integration, is also soaring: last year, estimated the United Nations Conference on Trade and Development, cross border investment increased by 40%, to $315 billion.